2014
DOI: 10.1111/febs.12894
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the structure and function of fungal β‐mannosidases from glycoside hydrolase family 2 based on multiple crystal structures of the Trichoderma harzianum enzyme

Abstract: Hemicellulose is an important part of the plant cell wall biomass, and is relevant to cellulosic ethanol technologies. b-Mannosidases are enzymes capable of cleaving nonreducing residues of b-D-mannose from b-D-mannosides and hemicellulose mannose-containing polysaccharides, such as mannans and galactomannans. b-Mannosidases are distributed between glycoside hydrolase (GH) families 1, 2, and 5, and only a handful of the enzymes have been structurally characterized to date. The only published X-ray structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…4, A and B) with a (␤/␣) 8 catalytic core at the central position. This modular organization is similar to that seen in other GH2 enzymes, such as ␤-mannosidases, from Bacteroides thetaiotaomicron (BtMan2A) (22), Dictyoglomus thermoplilum (DtMan) (23), and Trichoderma harzianum (ThMan2A) (24), and ␤-galactosidases, from E. coli (25) and Arthrobacter sp. (26).…”
Section: The Multi-modular Structural Architecture Biological Assembsupporting
confidence: 72%
See 1 more Smart Citation
“…4, A and B) with a (␤/␣) 8 catalytic core at the central position. This modular organization is similar to that seen in other GH2 enzymes, such as ␤-mannosidases, from Bacteroides thetaiotaomicron (BtMan2A) (22), Dictyoglomus thermoplilum (DtMan) (23), and Trichoderma harzianum (ThMan2A) (24), and ␤-galactosidases, from E. coli (25) and Arthrobacter sp. (26).…”
Section: The Multi-modular Structural Architecture Biological Assembsupporting
confidence: 72%
“…Domain I is colored in pale green, domain II in light blue, domain III in light orange, domain IV in light pink, and domain V in pale cyan. B, amino acid sequence alignment of XacMan2A with GH2 ␤-mannosidases from B. thetaiotaomicron (BtMan2A, 39%, PDB code 2JE8 (22)) and T. harzianum (ThMan2A, 25%, PDB code 4CVU(24). The five structural domains of XacMan2A are indicated in the amino acid sequence.…”
mentioning
confidence: 99%
“…A higher proportion of oligosaccharide-degrading enzymes are associated with an increased rate of monosaccharide and VFA generation, which promotes nutrient absorption and utilization by ruminants [5]. In this study, the most highly represented GH family was GH2 (which comprises β-Dgalactosidase, β-glucuronidase, β-D-mannosidase, and exo-β-glucosaminidase [38]) followed by the GH43 (which includes β-xylosidase, β-1,3-xylosidase, α-L-arabinofuranosidase, arabinanase, xylanase, galactan 1, and 3-β-galactosidase). Our results are in accordance with the finding that GH3 and GH2 are the predominant GHs in the rumen of Indian buffalo [3,35,36].…”
Section: Discussionmentioning
confidence: 78%
“…Studies have shown that b-mannosidases from GH families 2 and 5 possess two aglycone sugar binding subsites (?1 and ?2) and a glycone sugar binding subsite (-1) (Dias et al 2004;Tailford et al 2007). GH2 mannosidases have a conserved domain organization which consists of five domains, with the catalytic domain positioned in the center (Tailford et al 2007;Nascimento et al 2014), while GH5 mannosidases exhibit a simpler domain organization (Dias et al 2004). …”
Section: Mannosidasesmentioning
confidence: 99%
“…In both studies (Hägglund 2002;Shi et al 2011), where anti-synergy was observed when a mannanase and mannosidase combination was used simultaneously, the mannosidase used was always affiliated to GH family 2. GH2 mannosidases have been reported to have the ability to bind to galactomannan via putative non catalytic binding sites made up of polar pockets that can recognize and accommodate galactomannan (Kulminskaya et al 1999;Nascimento et al 2014). Surprisingly, these galactomannan binding pockets are not observed in GH5 mannosidases.…”
Section: Homeosynergistic Hydrolysis Of Mannans and Hetero-mannansmentioning
confidence: 99%